Semiconductor nanoparticles and method for producing same

The core-shell structured semiconductor nanoparticles with Group 11-13-16 elements address the issue of broad emission peaks in ternary and quaternary quantum dots by achieving band edge emission, suitable for high-color-reproducibility light-emitting devices, especially in liquid crystal displays, without toxic materials.

JP7607294B2Active Publication Date: 2024-12-27OSAKA UNIVERSITY +2
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
JP2023114401
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2016-09-12
Filing Date
2023-07-12
Publication Date
2024-12-27
Estimated Expiration
2037-02-28

AI Technical Summary

Technical Problem

Existing quantum dots, particularly ternary and quaternary quantum dots, do not exhibit band edge emission suitable for high-color-reproducibility light-emitting devices due to broad emission peaks and long luminescence lifetimes, which are unsuitable for liquid crystal displays, despite having low toxicity compositions.

Method used

Semiconductor nanoparticles with a core-shell structure are developed, where the core is made of Group 11-13-16 elements and coated with a shell of larger bandgap Group 13-16 elements, forming a heterojunction to achieve band edge emission.

Benefits of technology

The core-shell structure enables short luminescence lifetime and narrow emission peaks, making it suitable for high-color-reproducibility light-emitting devices, particularly in liquid crystal displays, without using toxic elements like Cd and Pb.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007607294000005
    Figure 0007607294000005
  • Figure 0007607294000006
    Figure 0007607294000006
  • Figure 0007607294000007
    Figure 0007607294000007
Patent Text Reader

Abstract

To provide a semiconductor nanoparticle having a constitution providing a band edge light emission from ternary system quantum dots with potential for low toxicity.SOLUTION: A semiconductor nanoparticle includes: a first semiconductor including M1, M2, and Z, where M1 is at least one element selected from the group consisting of Ag, Cu and Au, M2 is at least one element selected from the group consisting of Al, Ga, In and Tl, and Z is at least one element selected from the group consisting of S, Se and Te; and a second semiconductor that is disposed on the surface of the first semiconductor and has a band gap energy higher than that of the first semiconductor. The semiconductor nanoparticle has an emission lifetime of 200 ns or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to semiconductor nanoparticles and methods for making the same, as well as light-emitting devices using the semiconductor nanoparticles. [Background technology]

[0002] As a white light-emitting device to be used in the backlight of liquid crystal display devices, devices utilizing the emission of quantum dots (also called semiconductor quantum dots) have been proposed. It is known that when the particle size of semiconductor particles is, for example, 10 nm or less, the quantum size effect appears, and such nanoparticles are called quantum dots. The quantum size effect refers to the phenomenon in which the valence band and conduction band, which are considered continuous in bulk particles, become discrete when the particle size is nanosized, and the band gap energy changes depending on the particle size.

[0003] Quantum dots absorb light and emit light corresponding to the band gap energy, so they can be used as wavelength conversion materials in light-emitting devices. Light-emitting devices using quantum dots have been proposed in, for example, Patent Documents 1 and 2. Specifically, it has been proposed to absorb a part of the light emitted from an LED chip into quantum dots to emit light of a different color, and to obtain white light by mixing the light emitted from the quantum dots with the light from the LED chip that has not been absorbed by the quantum dots. These patent documents propose the use of quantum dots of Groups 12-16 such as CdSe and CdTe, and Groups 14-16 such as PbS and PbSe. In addition, Patent Document 3 proposes a wavelength conversion film using core-shell structured semiconductor quantum dots that do not contain Cd or Pb, taking into account the toxicity of compounds containing these elements. The core-shell structure is also described in Non-Patent Document 1. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2012-212862 A [Patent Document 2] JP 2010-177656 A [Patent Document 3] WO2014 / 129067 [Non-patent literature]

[0005] [Non-Patent Document 1] Chem, Commun. 2010, vol. 46, pp 2082-2084 Summary of the Invention [Problem to be solved by the invention]

[0006] One of the advantages of using quantum dots in light-emitting devices is that light with a wavelength corresponding to the band gap can be obtained as a peak with a relatively narrow half-width. However, among the quantum dots proposed as wavelength conversion materials, only those made of binary semiconductors such as CdSe, which are typified by Group 12-14 elements, have been confirmed to emit light with a wavelength corresponding to the band gap. However, band-edge emission has not been confirmed for ternary quantum dots, particularly quantum dots made of Group 11-13-16 elements.

[0007] The light emitted from quantum dots of the 11th, 13th, and 16th groups originates from defect levels on the particle surface or inside, or from donor-acceptor pair recombination, and therefore has a broad emission peak with a wide half-width and a long emission lifetime. Such emission is not suitable for light-emitting devices used in liquid crystal displays, in particular. This is because light-emitting devices used in liquid crystal displays require emission with a narrow half-width and peak wavelengths corresponding to the three primary colors (RGB) to ensure high color reproducibility. Therefore, although ternary quantum dots can be made into a low-toxicity composition, their practical use has not progressed.

[0008] An object of the embodiments of the present invention is to provide semiconductor nanoparticles and a method for producing the same that are configured to obtain band edge emission from ternary or quaternary quantum dots that can have a low toxicity composition. [Means for solving the problem]

[0009] An embodiment of the present invention is a semiconductor nanoparticle that emits light when irradiated with light, the semiconductor nanoparticle comprising a core and a shell that covers the surface of the core, has a band gap energy larger than that of the core, and is heterojunction with the core, the shell comprising: 1 , M 2 and Z, 1 is at least one element selected from the group consisting of Ag, Cu and Au, and M 2 is at least one element selected from the group consisting of Al, Ga, In and Tl, and Z is at least one element selected from the group consisting of S, Se and Te, and the shell is a semiconductor consisting essentially of a Group 13 element and a Group 16 element.

[0010] Further, an embodiment of the present invention is 1 , M 2 and Z, 1 is at least one element selected from the group consisting of Ag, Cu and Au, and M 2 preparing a dispersion liquid in which primary semiconductor nanoparticles made of a semiconductor, wherein Z is at least one element selected from the group consisting of Al, Ga, In, and Tl, and Z is at least one element selected from the group consisting of S, Se, and Te, are dispersed in a solvent; The method for producing semiconductor nanoparticles includes adding a compound containing a Group 13 element and a simple substance of a Group 16 element or a compound containing a Group 16 element to the dispersion liquid, and forming a semiconductor layer consisting essentially of the Group 13 element and the Group 16 element on the surface of the primary semiconductor nanoparticles. Effect of the Invention

[0011] The semiconductor nanoparticles according to the embodiment of the present invention are characterized in that the surface of a core made of a specific ternary semiconductor is covered with a shell made of a semiconductor containing a group 13 element and a group 16 element, which has a larger band gap energy than the semiconductor. This feature makes it possible to obtain light emission with a short emission life, i.e., band edge emission, which has not been obtained with the ternary quantum dots in the past. Both the core and the shell of the semiconductor nanoparticles can be made of a composition that does not contain Cd and Pb, which are considered to be highly toxic, and the semiconductor nanoparticles can be applied to products in which the use of Cd and the like is prohibited. Therefore, the semiconductor nanoparticles can be suitably used as a wavelength conversion material for light-emitting devices used in liquid crystal displays and the like, and as a biomolecular marker. Furthermore, according to the above-mentioned method for producing semiconductor nanoparticles, it becomes possible to relatively easily produce ternary semiconductor nanoparticles that give band edge emission. [Brief description of the drawings]

[0012] [Figure 1] 1 shows an XRD pattern of the primary semiconductor nanoparticles (core) produced in Example 1. [Diagram 2] 1 shows an emission spectrum of semiconductor nanoparticles having a core-shell structure prepared in Example 1. [Diagram 3] 1 shows absorption and excitation spectra of semiconductor nanoparticles having a core-shell structure prepared in Example 1. [Figure 4] 1 shows an emission spectrum of the primary semiconductor nanoparticles (core) produced in Example 1. [Diagram 5] 1 shows an absorption spectrum of the primary semiconductor nanoparticles (core) produced in Example 1. [Figure 6] 1 shows an emission spectrum of semiconductor nanoparticles having a core-shell structure prepared in Example 2. [Figure 7] 1 shows absorption and excitation spectra of semiconductor nanoparticles having a core-shell structure prepared in Example 2. [Figure 8] 1 shows an emission spectrum of semiconductor nanoparticles having a core-shell structure prepared in Example 3. [Figure 9]1 shows absorption and excitation spectra of semiconductor nanoparticles having a core-shell structure prepared in Example 3. [Figure 10] 1 shows an emission spectrum of the semiconductor nanoparticles produced in Comparative Example 1. [Figure 11] 1 shows an absorption spectrum of the semiconductor nanoparticles produced in Comparative Example 1. [Figure 12] 1 shows emission spectra of the semiconductor nanoparticles produced in Examples 4A to 4D. [Figure 13] 1 shows emission spectra of the semiconductor nanoparticles produced in Examples 5A to 5F. [Figure 14] 1 is a graph showing the relationship between the peak intensity of band edge emission and retention time for the semiconductor nanoparticles produced in Examples 4A to 4D and Examples 5A to 5F. [Figure 15] 1 is a graph showing the relationship between the peak wavelength of band edge emission and retention time for the semiconductor nanoparticles produced in Examples 4A to 4D and 5A to 5F. [Figure 16] 1 is an HRTEM image of the semiconductor nanoparticles produced in Example 5F. [Figure 17] 1 is an HAADF image of the semiconductor nanoparticles produced in Example 5F. [Figure 18] 1 shows an emission spectrum of semiconductor nanoparticles having a core-shell structure prepared in Example 6. [Figure 19] 1 shows an absorption spectrum of semiconductor nanoparticles having a core-shell structure prepared in Example 6. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] The embodiments are described in detail below. However, the present invention is not limited to the following embodiments. Furthermore, the matters described in each embodiment and its modified example can be applied to other embodiments and modified examples, unless otherwise specified.

[0014] (Outline of this embodiment) The present inventors have investigated a configuration for obtaining band-edge emission from ternary quantum dots, particularly quantum dots of group 11-group 13-group 16, which have not been confirmed to exhibit band-edge emission when produced by a general production method. In the course of the investigation, the present inventors have investigated the possibility of obtaining band-edge emission by changing the surface state of ternary or quaternary quantum dots, and in particular, have investigated changing the surface state by covering the surface of the quantum dots with an appropriate semiconductor. As a result, they have found that band-edge emission can be obtained from ternary or quaternary quantum dots by covering the quantum dots with a semiconductor containing a group 13 element and a group 16 element, and have arrived at this embodiment. As for CdSe, for which band-edge emission has been confirmed, a configuration has already been proposed in which the surface is coated with CdS or the like in order to enhance the band-edge emission. Also, for ternary quantum dots, a configuration has been proposed in which the surface is coated with ZnS or ZnSe or the like. However, there have been no reports to date of band-edge emission being obtained by using a ternary or quaternary quantum dot core that does not produce band-edge emission or in which band-edge emission is hardly observed in the emission spectrum, and coating the surface of the core with a shell made of a specific semiconductor.

[0015] The semiconductor nanoparticles of this embodiment are 1 , M 2 and Z, 1 is at least one element selected from the group consisting of Ag, Cu and Au, and M 2 The surface of a core made of a semiconductor in which Z is at least one element selected from the group consisting of S, Se and Te is covered with a shell that is substantially a semiconductor made of Group 13 elements and Group 16 elements and has a larger band gap energy than the core, and the shell is heterojunctioned with the core. In the following, the core (ternary and quaternary systems) and the shell will be described first.

[0016] [core] (Ternary core) The core, which is made of a ternary semiconductor, is M 1 , M 2 , and Z and takes the form of a particle itself, and is therefore a semiconductor nanoparticle. Here, M 1 is at least one element selected from the group consisting of Ag, Cu and Au, preferably Ag or Cu, and particularly preferably Ag. 1 When M is Ag, it becomes easy to synthesize the core (corresponding to the primary semiconductor nanoparticles used in the manufacturing method described later). 1 Two or more elements may be included as the element. The crystal structure of the core may be at least one selected from the group consisting of tetragonal, hexagonal, and orthorhombic.

[0017] M 2 is at least one element selected from the group consisting of Al, Ga, In and Tl, preferably In or Ga, and particularly preferably In. In is preferred because it is less likely to produce by-products. 2 Two or more elements may be included as the element.

[0018] Z is at least one element selected from the group consisting of S, Se, and Te, and is preferably S. A core in which Z is S has a wider band gap than one in which Z is Se or Te, and is therefore preferred because it is more likely to emit light in the visible light region. Z may contain two or more elements.

[0019] M 1 , M 2 The combination of and Z is not particularly limited. 1 , M 2 and Z combinations (M 1 / M 2 / Z) is preferably Cu / In / S, Ag / In / S, Ag / In / Se, and Ag / Ga / S.

[0020] Semiconductors that contain the above-mentioned specific elements and have a tetragonal, hexagonal, or orthorhombic crystal structure are generally referred to as M 1 M 2 It has been introduced in the literature as being represented by the composition formula Z2. 1 M 2 A semiconductor represented by the formula Z2 having a hexagonal crystal structure is a wurtzite type, and a semiconductor having a tetragonal crystal structure is a chalcopyrite type. The crystal structure is identified, for example, by measuring an XRD pattern obtained by X-ray diffraction (XRD). Specifically, the XRD pattern obtained from the core is 1 M 2 The XRD pattern is compared with a known XRD pattern of a semiconductor nanoparticle represented by the composition Z2, or an XRD pattern obtained by performing a simulation from the crystal structure parameters. If any of the known patterns and the simulated patterns matches the core pattern, the crystal structure of the semiconductor nanoparticle can be said to be the crystal structure of the matching known or simulated pattern. In an aggregate of semiconductor nanoparticles, multiple types of semiconductor nanoparticles having different core crystal structures may be present together, in which case peaks derived from multiple crystal structures will be observed in the XRD pattern.

[0021] However, the core made of a ternary semiconductor does not actually have the stoichiometric composition represented by the above general formula, and in particular M 1 Number of atoms vs. M 2 The ratio of the number of atoms (M 1 / M 2 ) is smaller than 1. Also, M 1 Number of atoms and M 2 The sum of the numbers of atoms of M and Z may not be the same as the number of atoms of Z. In the semiconductor nanoparticles of this embodiment, the core made of a ternary semiconductor may be made of such a semiconductor of non-stoichiometric composition. In this specification, when a semiconductor containing a specific element is used, and it does not matter whether it is stoichiometric or not, the term "M" is used. 1 -M 2 The composition of a semiconductor is expressed by a formula in which the constituent elements are connected with a "-" such as -Z.

[0022] The core is M 1 , M 2 and Z. Here, the term "substantially" means that the compound may be composed of M, Z, and Z only if it is inevitably composed of M, Z, and Z due to the inclusion of impurities or the like. 1 , M 2 It is used taking into consideration that elements other than Z are included.

[0023] Alternatively, the core may contain other elements, for example M 2 may be partially substituted with other metal elements. The other metal elements may be metal ions with a valence of +3, specifically, one or more elements selected from Cr, Fe, Al, Y, Sc, La, V, Mn, Co, Ni, Ga, In, Rh, Ru, Mo, Nb, W, Bi, As, and Sb. The amount of substitution is M 2 When the total number of atoms of the substituent elements and the substituted elements is taken as 100%, it is preferably 10% or less.

[0024] (Quaternary core) The core, which is made of a quaternary semiconductor, is M 1 , M 2 , M 3 , and Z, and is itself a semiconductor nanoparticle, like the core made of a ternary semiconductor. The crystal structure of the core made of a quaternary semiconductor may be at least one selected from the group consisting of tetragonal, hexagonal, and orthorhombic. In the nanoparticle aggregate, multiple types of nanoparticles having different core crystal structures may be mixed. In that case, peaks derived from multiple crystal structures are observed in the XRD pattern. M 1 , M 2 and Z are as explained in relation to the ternary core, and therefore will not be explained here. M 3 is at least one element selected from the group consisting of Zn and Cd. 3 is preferably Zn. 3When is Zn, the semiconductor nanoparticles of this embodiment can be provided as those having a low toxicity composition. Even when Cd is used, the amount of Cd can be reduced compared to a binary core using Cd, so that the semiconductor nanoparticles can be provided as those having a low toxicity composition.

[0025] M 1 , M 2 , M 3 and Z combinations (M 1 / M 2 / M 3 / Z) is not particularly limited. 1 , M 2 , M 3 and Z combinations (M 1 / M 2 / M 3 / Z) is preferably Cu / In / Zn / S, Ag / In / Zn / S.

[0026] Semiconductors that contain the above four specific elements and have a tetragonal, hexagonal, or orthorhombic crystal structure are generally referred to as (M 1 M 2 ) x M 3 y Z2 (where x+y=2) is introduced in the literature. That is, the semiconductor represented by this composition formula is the same as the M 1 M 2 In semiconductors with the formula Z2, M 3 doped or M 1 M 2 Z2 and M 3 It can be said that Z forms a solid solution.

[0027] Even when the core is made of a quaternary semiconductor, it is not actually of the stoichiometric composition represented by the above general formula, and in particular M 1 Number of atoms vs. M 2 The ratio of the number of atoms (M 1 / M 2) is smaller than 1. Also, x+y may not be 2. In the semiconductor nanoparticles of this embodiment, the core made of a quaternary semiconductor may be made of such a semiconductor of non-stoichiometric composition. Therefore, in this specification, the term M 1 -M 2 -M 3 The composition of a semiconductor is sometimes expressed by a formula in which the constituent elements are connected with "-", such as -Z. The method for identifying the crystal structure of a quaternary semiconductor is as described in relation to the core made of a ternary semiconductor.

[0028] The core, which is made of a quaternary semiconductor, is M 1 , M 2 , M 3 and Z. Here, the term "substantially" means that there is inevitably a part consisting of M and Z due to the inclusion of impurities, etc. 1 , M 2 、 M 3 The term is used taking into consideration that elements other than Z may be included. Alternatively, the core made of a quaternary semiconductor may contain other elements.

[0029] For example, M 2 A part of the above may be replaced by another metal element. Examples of the other metal elements and the amount of replacement are the same as those described in relation to the ternary core, so the description thereof will be omitted here.

[0030] Additionally / alternatively, M 3 may be partially substituted with another metal element. The other metal element may be a metal ion with a valence of +2, specifically, at least one element selected from Co, Ni, Pd, Sr, Ba, Fe, Cr, Mn, Cu, Cd, Rh, W, Ru, Pb, Sn, Mg, and Ca. The amount of substitution is determined by the following formula: 3 When the total number of atoms of the substituent elements and the substituted elements is taken as 100%, it is preferably 10% or less.

[0031] [shell] In this embodiment, the shell is a semiconductor having a larger band gap energy than the semiconductor constituting the core, and is a semiconductor substantially composed of Group 13 elements and Group 16 elements. Examples of Group 13 elements include B, Al, Ga, In, and Tl, and examples of Group 16 elements include O, S, Se, Te, and Po. The semiconductor constituting the shell may contain only one type of Group 13 element or two or more types of Group 16 element, and may contain only one type of Group 16 element or two or more types of Group 16 element. Specifically, "substantially" indicates that when the total number of atoms of all elements contained in the shell is 100%, the proportion of elements other than Group 13 elements and Group 16 elements is, for example, 5% or less.

[0032] The band gap energy of the semiconductor constituting the core depends on its composition, but ternary semiconductors of Group 11-Group 13-Group 16 or quaternary semiconductors based on these generally have a band gap energy of 1.0 eV to 3.5 eV. In particular, a semiconductor made of Ag-In-S has a band gap energy of 1.8 eV to 1.9 eV, and a semiconductor made of Ag-In-Zn-S has a band gap energy of 1.8 eV to 3.9 eV. Therefore, the shell may be configured by selecting its composition, etc., depending on the band gap energy of the semiconductor constituting the core. Alternatively, when the composition, etc. of the shell is determined in advance, the core may be designed so that the band gap energy of the semiconductor constituting the core is smaller than that of the shell.

[0033] Specifically, the shell may have a band gap energy of, for example, 2.0 eV to 5.0 eV, particularly 2.5 eV to 5.0 eV. The band gap energy of the shell may be, for example, about 0.1 eV to 3.0 eV, particularly about 0.3 eV to 3.0 eV, more particularly about 0.5 eV to 1.0 eV, larger than the band gap energy of the core. If the difference between the band gap energy of the shell and the band gap energy of the core is small, the proportion of emission other than the band edge emission may increase in the emission from the core, and the proportion of the band edge emission may decrease.

[0034] Furthermore, the band gap energy of the core and the shell is preferably selected so as to provide a type-I band alignment in which the band gap energy of the shell sandwiches the band gap energy of the core at the heterojunction of the core and the shell. By forming the type-I band alignment, it is possible to obtain better band edge emission from the core. In the type-I alignment, a barrier of at least 0.1 eV is preferably formed between the band gap of the core and the band gap of the shell, and a barrier of 0.2 eV or more, more particularly 0.3 eV or more may be formed. The upper limit of the barrier is, for example, 1.8 eV, and particularly 1.1 eV. If the barrier is small, the proportion of emission other than the band edge emission in the emission from the core may increase, and the proportion of the band edge emission may decrease.

[0035] In this embodiment, the shell may contain In or Ga as a Group 13 element. Also, in this embodiment, the shell may contain S as a Group 16 element. Semiconductors containing In or Ga or containing S tend to be semiconductors having a larger band gap energy than Group 11-Group 13-Group 16 ternary semiconductors.

[0036] The shell may also be a semiconductor whose crystal system is familiar to that of the core semiconductor, and whose lattice constant is the same or close to that of the core semiconductor. A shell made of a semiconductor whose crystal system is familiar and whose lattice constant is close (here, a shell whose lattice constant multiples are close to that of the core is also considered to be close) may well cover the periphery of the core. For example, Ag-In-S, a ternary semiconductor of Groups 11-13-16, is generally a tetragonal system, but examples of familiar crystal systems include the tetragonal system and the orthorhombic system. When the Ag-In-S semiconductor is a tetragonal system, its lattice constants are 5.828 Å, 5.828 Å, and 11.19 Å, and it is preferable that the shell covering it is a tetragonal or cubic system whose lattice constant or multiples are close to the lattice constant of the Ag-In-S semiconductor. Alternatively, the shell may be amorphous.

[0037] Whether or not an amorphous shell is formed can be confirmed by observing the semiconductor nanoparticles of the core-shell structure of this embodiment with HAADF-STEM. Specifically, a part having a regular pattern (for example, a striped pattern or a dot pattern, etc.) is observed in the center, and a part not observed as having a regular pattern is observed around it in HAADF-STEM. According to HAADF-STEM, a substance having a regular structure such as a crystalline substance is observed as an image having a regular pattern, and a substance not having a regular structure such as an amorphous substance is not observed as an image having a regular pattern. Therefore, when the shell is amorphous, the shell can be observed as a part that is clearly different from the core (which has a crystal structure such as a tetragonal system as described above) observed as an image having a regular pattern.

[0038] Furthermore, when the core is made of Ag-In-S and the shell is made of GaS, the shell tends to be observed as a darker image than the core in the image obtained by HAADF-STEM, because Ga is a lighter element than Ag and In.

[0039] Whether or not an amorphous shell is formed can also be confirmed by observing the semiconductor nanoparticles having the core-shell structure of this embodiment with a high-resolution transmission electron microscope (HRTEM). In an image obtained with HRTEM, the core portion is observed as a crystal lattice image (an image having a regular pattern), while the shell portion is observed as a portion in which a black and white contrast is observed but no regular pattern is visible.

[0040] On the other hand, it is preferable that the shell does not form a solid solution with the core. If the shell forms a solid solution with the core, the two become one, and the mechanism of this embodiment, in which the core is covered with the shell and the surface state of the core is changed to obtain band edge emission, is not obtained. For example, it has been confirmed that band edge emission cannot be obtained from the core even if the surface of a core made of Ag-In-S is covered with zinc sulfide (Zn-S) of stoichiometric composition or non-stoichiometric composition. In relation to Ag-In-S, Zn-S satisfies the above conditions regarding band gap energy and provides type-1 band alignment. Despite this, it is presumed that the reason why band edge emission was not obtained from the specific semiconductor is that the specific semiconductor and ZnS form a solid solution, and the core-shell interface disappears.

[0041] The shell may include, but is not limited to, a combination of In and S, a combination of Ga and S, or a combination of In, Ga and S, as a combination of Group 13 and Group 16 elements. The combination of In and S may be in the form of indium sulfide, and the combination of Ga and S may be in the form of gallium sulfide, and the combination of In, Ga and S may be indium gallium sulfide. Indium sulfide constituting the shell in this embodiment may not be of stoichiometric composition (In2S3), and in this sense, indium sulfide is referred to herein as having the formula InS x(x is not limited to an integer, but may be any number, for example, 0.8 to 1.5.) Similarly, gallium sulfide does not have to be of stoichiometric composition (Ga2S3), and in this sense, gallium sulfide is herein referred to as having the formula GaS x (x is not limited to integers, but may be any number between 0.8 and 1.5). Indium gallium sulfide is In 2(1-y) Ga 2y S3 (where y is any number greater than 0 and less than 1), or In a Ga 1-a S b (where a is any number greater than 0 and less than 1, and b is any number not limited to integers).

[0042] Indium sulfide has a band gap energy of 2.0 eV to 2.4 eV, and its lattice constant is 10.775 Å for a cubic crystal system. Gallium sulfide has a band gap energy of about 2.5 eV to 2.6 eV, and its lattice constant is 5.215 Å for a tetragonal crystal system. However, the crystal systems described here are all reported values, and the shells of actual core-shell semiconductor nanoparticles do not necessarily satisfy these reported values. Indium sulfide and gallium sulfide are preferably used as the semiconductor constituting the shell when the core is a ternary or quaternary semiconductor of Groups 11-13-16, particularly Ag-In-S or Ag-In-Zn-S. In particular, gallium sulfide is preferably used because of its larger band gap energy. When gallium sulfide is used, stronger band edge emission can be obtained compared to when indium sulfide is used.

[0043] The surface of the shell may be modified with any compound. When the surface of the shell is an exposed surface of a semiconductor nanoparticle having a core-shell structure, the surface can be modified to stabilize the nanoparticle and prevent the semiconductor nanoparticle from agglomerating or growing, and / or to improve the dispersibility of the semiconductor nanoparticle in a solvent.

[0044] The surface modifier may be, for example, a nitrogen-containing compound having a hydrocarbon group having 4 to 20 carbon atoms, a sulfur-containing compound having a hydrocarbon group having 4 to 20 carbon atoms, or an oxygen-containing compound having a hydrocarbon group having 4 to 20 carbon atoms. Examples of the hydrocarbon group having 4 to 20 carbon atoms include saturated aliphatic hydrocarbon groups such as n-butyl, isobutyl, n-pentyl, n-hexyl, octyl, decyl, dodecyl, hexadecyl, and octadecyl groups; unsaturated aliphatic hydrocarbon groups such as oleyl; alicyclic hydrocarbon groups such as cyclopentyl and cyclohexyl; and aromatic hydrocarbon groups such as phenyl, benzyl, naphthyl, and naphthylmethyl groups, among which saturated aliphatic hydrocarbon groups and unsaturated aliphatic hydrocarbon groups are preferred. Examples of the nitrogen-containing compound include amines and amides, examples of the sulfur-containing compound include thiols, and examples of the oxygen-containing compound include fatty acids.

[0045] As the surface modifier, a nitrogen-containing compound having a hydrocarbon group having 4 to 20 carbon atoms is preferred. Such nitrogen-containing compounds include, for example, alkylamines such as n-butylamine, isobutylamine, n-pentylamine, n-hexylamine, octylamine, decylamine, dodecylamine, hexadecylamine, and octadecylamine, and alkenylamines such as oleylamine. In particular, n-tetradecylamine is preferred because it is easy to obtain a compound with high purity and has a boiling point of more than 290°C.

[0046] The surface modifier is preferably a sulfur-containing compound having a hydrocarbon group having a carbon number of 4 to 20. Examples of such sulfur-containing compounds include n-butanethiol, isobutanethiol, n-pentanethiol, n-hexanethiol, octanethiol, decanethiol, dodecanethiol, hexadecanethiol, and octadecanethiol.

[0047] The surface modifier may be used in combination of two or more different ones. For example, one compound selected from the nitrogen-containing compounds exemplified above (e.g., oleylamine) and one compound selected from the sulfur-containing compounds exemplified above (e.g., dodecanethiol) may be used in combination.

[0048] [Core-shell structure] The configuration of the semiconductor nanoparticles having a core-shell structure according to this embodiment, which are composed of the above-described core and shell, will be described below.

[0049] The core-shell semiconductor nanoparticles of this embodiment may have an average particle size of, for example, 50 nm or less, within the range of 1 nm to 20 nm, and particularly within the range of 1 nm to 10 nm.

[0050] The average particle size of nanoparticles may be determined, for example, from a TEM image taken using a transmission electron microscope (TEM). Specifically, the particle size of nanoparticles refers to the longest line segment among those that connect any two points on the periphery of a particle observed in a TEM image and pass through the center of the particle.

[0051] However, when the particle has a rod-like shape, the length of the minor axis is regarded as the particle size. Here, the rod-like particle refers to a particle that is observed as a quadrangle including a rectangular shape (the cross section has a circular, elliptical, or polygonal shape), an elliptical shape, or a polygonal shape (for example, a pencil-like shape), and the ratio of the length of the major axis to the length of the minor axis is greater than 1.2. For a particle having a rod-like shape, the length of the major axis refers to the longest line segment among any two points on the periphery of the particle in the case of an elliptical shape, and refers to the longest line segment among the lines that are parallel to the longest side that defines the periphery and that connects any two points on the periphery of the particle in the case of a rectangular or polygonal shape. The length of the minor axis refers to the line segment that is perpendicular to the line segment that defines the length of the major axis and that has the longest length among the lines that connect any two points on the periphery.

[0052] The average particle size is determined by acquiring TEM images at 50,000 to 150,000 times magnification at three or more points on an arbitrarily selected grid, measuring the particle size of all measurable nanoparticles in each acquired TEM image, and taking the arithmetic average of those particle sizes. Here, a "measurable" particle is one whose entirety can be observed in a TEM image. Therefore, a particle that is not partly included in the imaging range in a TEM image and is "cut off" is not measurable. The number of TEM images is three or more, and the total number of nanoparticles included in the selected TEM images is 100 or more. Therefore, for example, if three TEM images appear to contain 100 or more nanoparticles, but in reality there are less than 100 nanoparticles, it is necessary to increase the number of imaging points. Alternatively, even if two TEM images contain 100 or more nanoparticles, the measurement of the average particle size of the nanoparticles is performed using three or more TEM images.

[0053] In the core-shell semiconductor nanoparticles, the core may have an average particle size of, for example, 10 nm or less, particularly 8 nm or less. The average particle size of the core may be within the range of 2 nm to 10 nm, particularly 2 nm to 8 nm, more particularly 2 nm to 6 nm, or within the range of 4 nm to 10 nm, or 5 nm to 8 nm. If the average particle size of the core is too large, it becomes difficult to obtain the quantum size effect and band edge emission.

[0054] The shell may have a thickness of 0.1 nm or more. The shell thickness may be in the range of 0.1 nm to 50 nm, particularly in the range of 0.1 nm to 20 nm, and more particularly in the range of 0.2 nm to 10 nm. Alternatively, the shell thickness may be in the range of 0.1 nm to 3 nm, and particularly in the range of 0.3 nm to 3 nm. If the shell thickness is too small, the effect of the shell covering the core is not sufficiently obtained, making it difficult to obtain band edge emission.

[0055] The average particle size of the core and the thickness of the shell may be determined by observing the core-shell semiconductor nanoparticles, for example, with HAADF-STEM. In particular, when the shell is amorphous, the thickness of the shell, which is easily observed as a part different from the core, can be easily determined with HAADF-STEM. In this case, the particle size of the core can be determined according to the method described above for the semiconductor nanoparticles. When the shell thickness is not constant, the smallest thickness is taken as the shell thickness of the particle.

[0056] Alternatively, the average particle size of the core may be measured in advance before coating with the shell, and the thickness of the shell may be determined by measuring the average particle size of the core-shell semiconductor nanoparticles and calculating the difference between the average particle size and the previously measured average particle size of the core.

[0057] The semiconductor nanoparticles of this embodiment emit light when irradiated with light, specifically, when irradiated with ultraviolet light, visible light, or infrared light, they emit light with a wavelength longer than that of the irradiated light. The emission of the semiconductor nanoparticles of this embodiment may be fluorescent or may include fluorescence. In that case, the semiconductor nanoparticles of this embodiment may function as fluorescent materials that emit fluorescence. In addition, the semiconductor nanoparticles of this embodiment can provide band edge emission from the core that does not emit band edge emission when not covered with a shell due to the core being covered with a shell containing an element of a specific group. Specifically, when the semiconductor nanoparticles of this embodiment are irradiated with, for example, ultraviolet light, visible light, or infrared light, they can emit light having a wavelength longer than that of the irradiated light, and the emission lifetime of the main component is 200 ns or less and / or the half width of the emission spectrum is 50 nm or less. Here, the "emission lifetime" refers to the lifetime of emission measured using an apparatus called a fluorescence lifetime measuring apparatus, as in the examples described later.

[0058] The above-mentioned "luminescence lifetime of the main component" is obtained according to the following procedure. First, the semiconductor nanoparticles are irradiated with excitation light to emit light, and the time-dependent change in attenuation (afterglow) of light with a wavelength near the peak of the emission spectrum, for example, a wavelength within the range of (peak wavelength ±50 nm), is measured. The time-dependent change is measured from the point in time when irradiation with the excitation light is stopped. The obtained decay curve is generally a sum of multiple decay curves derived from relaxation processes such as emission and heat. Therefore, in this embodiment, assuming that three components (i.e., three decay curves) are included, parameter fitting is performed so that the decay curve can be expressed by the following formula when the emission intensity is I(t). Parameter fitting is performed using dedicated software. I(t)=A1exp(-t / τ1)+A2exp(-t / τ2)+A3exp(-t / τ3)

[0059] In the above formula, τ1, τ2, and τ3 of each component are the time required for the emission intensity to decay to 1 / e (36.8%) of the initial value, which corresponds to the emission lifetime of each component. The emission lifetimes are set to τ1, τ2, and τ3 in order of shortest emission lifetime. Also, A1, A2, and A3 are the contribution rates of each component. In this embodiment, A x exp(-t / τ x When the main component has the largest integral value of the curve represented by A, the emission lifetime τ of the main component is 200 ns or less. Such emission is presumed to be band edge emission. x exp(-t / τ x ) from 0 to infinity x ×τ x The component with the largest value is selected as the principal component.

[0060] In this embodiment, the deviation between the decay curves drawn by the equations obtained by performing parameter fitting assuming that the luminescence decay curve contains three, four, or five components and the actual decay curve is not so different. Therefore, in this embodiment, when determining the luminescence lifetime of the main component, the number of components contained in the luminescence decay curve is assumed to be three, thereby avoiding the parameter fitting from becoming complicated.

[0061] The band edge emission may be obtained together with the defect emission. The defect emission generally has a long emission lifetime, a broad spectrum, and a peak on the longer wavelength side than the band edge emission. Alternatively, the semiconductor nanoparticles of this embodiment may emit only defect emission and not band edge emission. Even in such semiconductor nanoparticles, the core is covered with a shell, so that electrical defects on the surface are eliminated, making them more suitable and useful as materials (particularly, materials constituting solar cells) that perform charge separation and suppress recombination for the purpose of photoelectric conversion.

[0062] The intensity and peak position of the band edge emission emitted by the semiconductor nanoparticles of this embodiment can be changed by changing the particle size of the semiconductor nanoparticles. For example, the intensity of the band edge emission (ratio of band edge emission / defect emission intensity) can be increased by making the particle size of the semiconductor nanoparticles smaller. In addition, the peak wavelength of the band edge emission tends to shift to the short wavelength side by making the particle size of the semiconductor nanoparticles smaller. Furthermore, the half width of the spectrum of the band edge emission tends to become smaller by making the particle size of the semiconductor nanoparticles smaller.

[0063] The semiconductor nanoparticles of this embodiment are also preferably those whose absorption spectrum or excitation spectrum (also called fluorescence excitation spectrum) shows an exciton peak. The exciton peak is a peak obtained by exciton generation, and the fact that it appears in the absorption spectrum or excitation spectrum means that the particle size distribution is small and the particles are suitable for band edge emission with few crystal defects. The steeper the exciton peak, the more particles with uniform particle size and few crystal defects are contained in the semiconductor nanoparticle aggregate, and therefore the half width of the emission becomes narrower, and the emission efficiency is expected to improve. In the absorption spectrum or excitation spectrum of the semiconductor nanoparticles of this embodiment, the exciton peak is observed, for example, within the range of 350 nm to 1000 nm. The excitation spectrum for observing the presence or absence of the exciton peak may be measured by setting the observation wavelength near the peak wavelength.

[0064] [Method for producing semiconductor nanoparticles with core-shell structure] The core-shell semiconductor nanoparticles of this embodiment are - preparing a dispersion in a solvent of core semiconductor nanoparticles (for convenience, the cores before being coated with a shell are referred to herein as "primary semiconductor nanoparticles"); and - adding to the dispersion a compound containing the Group 13 element as a source of the same, and a simple substance of the Group 16 element or a compound containing the same as a source of the same, thereby forming a semiconductor layer consisting essentially of the Group 13 element and the Group 16 element on the surface of the primary semiconductor nanoparticles. Includes.

[0065] (Preparation of primary semiconductor nanoparticles) The primary semiconductor nanoparticles correspond to the cores described above, and in the case of ternary systems, M 1 , M 2 , and Z, and in the case of a quaternary system, M 1 , M 2 , M 3 The primary semiconductor nanoparticles are nanoparticles made of semiconductors containing M and Z. The primary semiconductor nanoparticles may be commercially available or may be produced experimentally, or may be produced by using commercially available nanoparticles. 1 Source, M. 2 source, and Z source, and optionally M 3 In the production method of the present embodiment, it is not necessary to immediately cover the primary semiconductor nanoparticles with a shell after the primary semiconductor nanoparticles are produced, and separately produced primary semiconductor nanoparticles may be used after a certain period of time.

[0066] Ternary primary semiconductor nanoparticles may be, for example, 1 Salts and element M 2 The compound may be prepared by a method including mixing a salt of the formula (I) with a ligand having the element Z as a coordination element to form a complex, and then subjecting the complex to a heat treatment. 1 salt and M 2 The salts are not particularly limited in type, and may be either organic acid salts or inorganic acid salts. Specifically, the salts may be any of nitrates, acetates, sulfates, hydrochlorides, and sulfonates, and are preferably organic acid salts such as acetates. This is because organic acid salts have high solubility in organic solvents and tend to make the reaction proceed more uniformly.

[0067] When Z is sulfur (S), examples of the ligand having Z as a coordinating element include β-dithiones such as 2,4-pentanedithione; dithiols such as 1,2-bis(trifluoromethyl)ethylene-1,2-dithiol; diethyldithiocarbamate; and thiourea.

[0068] When Z is tellurium (Te), examples of the ligand having Z as a coordination element include diallyl telluride and dimethyl ditelluride. When Z is selenium (Se), examples of the ligand having Z as a coordination element include dimethyl diselenocarbamic acid and 2-(dimethylamino)ethane selenol.

[0069] The complex is M 1 Salt, M 2 The complex is formed by mixing a salt of M with a ligand having Z as a coordination element. 1 salt and M 2 or by mixing an aqueous solution of a salt of M with an aqueous solution of the ligand. 1 Salt, M 2 The salt and the ligand may be mixed in an organic solvent (particularly, a highly polar organic solvent such as ethanol). The organic solvent may be a surface modifier or a solution containing a surface modifier. 1 Salt, M 2 The ratio of the salt and the ligand with Z as the coordination element is M 1 M 2 Corresponding to the composition formula of Z2, it is preferable to set the molar ratio to 1:1:2.

[0070] Next, the obtained complex is heat-treated to form primary semiconductor nanoparticles. The heat treatment of the complex may be carried out by precipitating and separating the obtained complex, drying it to obtain a powder, and heating the powder at a temperature of, for example, 100°C to 300°C. In this case, it is preferable that the primary semiconductor nanoparticles obtained by the heat treatment are further heat-treated in a solvent that is a surface modifier or a solvent containing a surface modifier to modify the surface. Alternatively, the heat treatment of the complex may be carried out by heating the complex obtained as a powder in a solvent that is a surface modifier or a solvent containing a surface modifier at a temperature of, for example, 100°C to 300°C. Alternatively, M 1 Salt, M 2 When the complex is formed by a method of adding the salt and the ligand to an organic solvent and mixing them, the organic solvent is used as the surface modifier or a solvent containing the surface modifier, and then the salt and the ligand are added, and then a heat treatment is performed, so that the formation of the complex, the heat treatment, and the surface modification may be performed successively or simultaneously.

[0071] Alternatively, the primary semiconductor nanoparticles may be M 1 Salt, M 2 The salt of M may be formed by adding the compound that provides Z to an organic solvent. 1 and then reacting the salt with an organic solvent to form a complex. 2 The compound may be produced by reacting a salt of M with a compound serving as a source of Z to form complexes, reacting these complexes with a compound serving as a source of Z, and then subjecting the resulting reaction product to crystal growth. 1 salts, and M 2 The salts of are as explained in relation to the preparation method including the formation of the above complex. The organic solvents that react with these salts to form complexes are, for example, alkylamines, alkenylamines, alkylthiols, alkenylamines, alkylphosphines, and alkenylphosphines having 4 to 20 carbon atoms. These organic solvents ultimately serve to modify the surface of the primary semiconductor nanoparticles obtained. These organic solvents may be mixed with other organic solvents. In this preparation method as well, M 1 Salt, M 2 The ratio of the salt of and the compound that supplies Z is 1 M2 Corresponding to the composition formula of Z2, it is preferable to set the molar ratio to 1:1:2.

[0072] When Z is sulfur (S), the compound serving as the supply source of Z is, for example, sulfur, thiourea, thioacetamide, or alkylthiol. When Z is tellurium (Te), for example, a Te-phosphine complex obtained by heat-treating a mixed solution of Te powder added to trialkylphosphine at 200 to 250°C may be used as the compound serving as the supply source of Z. When Z is selenium (Se), for example, a Se-phosphine complex obtained by heat-treating a mixed solution of Se powder added to trialkylphosphine at 200 to 250°C may be used as the compound serving as the supply source of Z.

[0073] Alternatively, the method for producing primary semiconductor nanoparticles may be a so-called hot injection method. In the hot injection method, compounds (e.g., M 1 Salt, M 2 This is a method for producing semiconductor nanoparticles in which a liquid (also called a precursor solution) in which a salt of and a compound serving as a source of Z (or a ligand with Z as a coordination element) are dissolved or dispersed is added in a relatively short time (for example, on the order of milliseconds) to generate many crystal nuclei at the beginning of the reaction. Alternatively, in the hot injection method, compounds serving as sources of some elements may be dissolved or dispersed in an organic solvent in advance, which may then be heated before the precursor solution of the other elements is added. If the solvent is a surface modifier or a solvent containing a surface modifier, surface modification can also be performed at the same time. According to the hot injection method, nanoparticles with smaller particle sizes can be produced.

[0074] The surface modifier that modifies the surface of the primary semiconductor nanoparticles is as described above in relation to the shell. When the primary semiconductor nanoparticles are surface-modified, the particles are stabilized, the aggregation or growth of the particles is prevented, and / or the dispersibility of the particles in the solvent is improved. When the primary semiconductor nanoparticles are surface-modified, the shell grows at the timing when the surface modifier is desorbed. Therefore, the surface modifier that modifies the primary semiconductor nanoparticles is usually not present on the surface of the core (the interface between the core and the shell) in the nanoparticles with a core-shell structure that are finally obtained.

[0075] Regardless of which manufacturing method is adopted, the production of the primary semiconductor nanoparticles is carried out in an inert atmosphere, particularly an argon atmosphere or a nitrogen atmosphere, in order to reduce or prevent the by-production of oxides and the oxidation of the surfaces of the primary semiconductor nanoparticles.

[0076] The primary semiconductor nanoparticles are 1 , M 2 , and Z, plus M 3 In the case of a quaternary system, that is, a quaternary system, in the production of the primary semiconductor nanoparticles described above, 3 salt, M 1 salt and M 2 Used with salt of M 1 Salt, M 2 Salt, M 3 The ratio of the salt of Z to the ligand having Z as a coordination element or the compound that supplies Z is (M 1 M 2 ) x M 3 y It is preferable that the molar ratio is x:x:y:2, which corresponds to the stoichiometric composition formula of Te2 (where x+y=2). 3 The salt of M may be either an organic acid salt or an inorganic acid salt. 3 The salt of may be any of nitrate, acetate, sulfate, hydrochloride, and sulfonate. The rest is the same as in the method for producing ternary primary semiconductor nanoparticles, so detailed description thereof will be omitted here.

[0077] Ternary or quaternary semiconductor nanoparticles are 2 In the case where a part of M is substituted with another metal element, a salt of the other metal element is used during the production of the primary semiconductor nanoparticles. In this case, M is adjusted so that the amount of the metal element substituted is as desired. 2 Similarly, when producing quaternary semiconductor nanoparticles, the composition is adjusted to M 3 When a part of the above is substituted with another metal element, a salt of the other metal element is used during the production of the primary semiconductor nanoparticles.

[0078] The ternary or quaternary primary semiconductor nanoparticles prepared by the above method may be separated from the solvent after the reaction is completed, and may be further purified as necessary. For example, the separation is performed by centrifuging the mixture after the particles are prepared and removing the supernatant. The purification may be performed by adding alcohol to the supernatant, centrifuging to cause precipitation, removing the precipitate (or removing the supernatant), and drying the separated precipitate, for example, by vacuum degassing or natural drying, or dissolving it in an organic solvent. The purification (addition of alcohol and centrifugation) may be performed multiple times as necessary. As the alcohol used for purification, a lower alcohol such as methanol, ethanol, or n-propanol may be used. When the precipitate is dissolved in an organic solvent, chloroform, toluene, cyclohexane, hexane, pentane, octane, or the like may be used as the organic solvent.

[0079] When the primary semiconductor nanoparticles are dried after purification, the drying may be performed by vacuum degassing, or by natural drying, or by a combination of vacuum degassing and natural drying. Natural drying may be performed, for example, by leaving the nanoparticles in the atmosphere at room temperature and pressure, in which case the nanoparticles may be left for 20 hours or more, for example, about 30 hours.

[0080] (Dispersion of primary semiconductor nanoparticles) When the primary semiconductor nanoparticles are coated with a shell, a dispersion liquid is prepared by dispersing the primary semiconductor nanoparticles in an appropriate solvent, and a semiconductor layer that becomes the shell is formed in the dispersion liquid. In the liquid in which the primary semiconductor nanoparticles are dispersed, no scattered light occurs, so the dispersion liquid is generally obtained as a transparent one (colored or colorless). The solvent in which the primary semiconductor nanoparticles are dispersed is not particularly limited, and may be any organic solvent (particularly, an organic solvent with high polarity such as ethanol) as in the case of preparing the primary semiconductor nanoparticles. The organic solvent may be a surface modifier or a solution containing a surface modifier. For example, the organic solvent may be at least one selected from nitrogen-containing compounds having a hydrocarbon group with 4 to 20 carbon atoms, which is the surface modifier described in relation to the shell, or at least one selected from sulfur-containing compounds having a hydrocarbon group with 4 to 20 carbon atoms, or a combination of at least one selected from nitrogen-containing compounds having a hydrocarbon group with 4 to 20 carbon atoms and at least one selected from sulfur-containing compounds having a hydrocarbon group with 4 to 20 carbon atoms. As the nitrogen-containing compound, n-tetradecylamine is particularly preferred because it is easily available in high purity and has a boiling point of over 290° C. Specific organic solvents include oleylamine, n-tetradecylamine, dodecanethiol, or a combination thereof.

[0081] The dispersion of primary semiconductor nanoparticles may be prepared so that the ratio of particles in the dispersion is, for example, 0.02% by mass to 1% by mass, particularly 0.1% by mass to 0.6% by mass. If the ratio of particles in the dispersion is too small, it becomes difficult to recover the product by the aggregation and precipitation process in a poor solvent, whereas if it is too large, the ratio of Ostwald ripening of the material constituting the core and fusion due to collision increases, and the particle size distribution tends to become broader.

[0082] (Shell formation) The semiconductor layer that becomes the shell is formed by adding a compound containing a Group 13 element and a simple substance of a Group 16 element or a compound containing a Group 16 element to the above dispersion. The compound containing a Group 13 element is a source of the Group 13 element, and is, for example, an organic salt, an inorganic salt, or an organometallic compound of the Group 13 element. Specifically, the compound containing a Group 13 element includes a nitrate, an acetate, a sulfate, a hydrochloride, a sulfonate, and an acetylacetonato complex, and is preferably an organic salt such as an acetate, or an organometallic compound. This is because the organic salt and the organometallic compound have high solubility in an organic solvent, and are likely to cause the reaction to proceed more uniformly.

[0083] A simple substance of a Group 16 element or a compound containing a Group 16 element is a source of the Group 16 element. For example, when sulfur (S) is used as a constituent element of the shell as the Group 16 element, simple sulfur such as high purity sulfur can be used, or a sulfur-containing compound such as thiols such as n-butanethiol, isobutanethiol, n-pentanethiol, n-hexanethiol, octanethiol, decanethiol, dodecanethiol, hexadecanethiol, or octadecanethiol, a disulfide such as dibenzyl disulfide, thiourea, or a thiocarbonyl compound can be used.

[0084] When oxygen (O) is used as the group 16 element for the shell, alcohols, ethers, carboxylic acids, ketones, and N-oxide compounds may be used as the group 16 element source. When selenium (Se) is used as the group 16 element for the shell, simple selenium, selenized phosphine oxide, organic selenium compounds (dibenzyl diselenide and diphenyl diselenide), hydrides, and other compounds may be used as the group 16 element source. When tellurium (Te) is used as the group 16 element for the shell, simple tellurium, tellurized phosphine oxide, or hydrides may be used as the group 16 element source.

[0085] The method of adding the Group 13 element source and the Group 16 element source to the dispersion liquid is not particularly limited. For example, a mixed liquid in which the Group 13 element source and the Group 16 element source are dispersed or dissolved in an organic solvent is prepared, and the mixed liquid may be added to the dispersion liquid little by little, for example, by a method of dropping. In this case, the mixed liquid may be added at a rate of 0.1 mL / hour to 10 mL / hour, particularly 1 mL / hour to 5 mL / hour. The mixed liquid may be added to a heated dispersion liquid. Specifically, for example, the dispersion liquid is heated so that its peak temperature becomes 200°C to 290°C, and after the peak temperature is reached, the mixed liquid is added little by little while maintaining the peak temperature, and then the temperature is lowered, thereby forming a shell layer (slow injection method). The peak temperature may be maintained as necessary even after the addition of the mixed liquid is completed.

[0086] If the peak temperature is too low, the surface modifier modifying the primary semiconductor nanoparticles may not be sufficiently removed, or the chemical reaction for generating the shell may not proceed sufficiently, resulting in insufficient formation of the semiconductor layer (shell). If the peak temperature is too high, the primary semiconductor nanoparticles may be altered, and band edge emission may not be obtained even if the shell is formed. The time for holding the peak temperature may be 1 minute to 300 minutes in total, particularly 10 minutes to 60 minutes, from the start of addition of the mixed liquid. The holding time of the peak temperature is selected in relation to the peak temperature, and a longer holding time is selected when the peak temperature is lower, and a shorter holding time is selected when the peak temperature is higher, which makes it easier to form a good shell layer. The rate of temperature increase and temperature decrease are not particularly limited, and the temperature decrease may be performed, for example, by holding the peak temperature for a predetermined time, and then turning off the heating source (e.g., electric heater) and allowing it to cool.

[0087] Alternatively, the Group 13 element source and the Group 16 element source may be added directly in their entirety to the dispersion. Then, the dispersion to which the Group 13 element source and the Group 16 element source have been added may be heated to form a shell semiconductor layer on the surface of the primary semiconductor nanoparticles (heating-up method). Specifically, the dispersion to which the Group 13 element source and the Group 16 element source have been added may be heated, for example, by gradually increasing the temperature until the peak temperature reaches 200°C to 290°C, and then by gradually decreasing the temperature after maintaining the peak temperature for 1 minute to 300 minutes. The rate of temperature increase may be, for example, 1°C / min to 50°C / min, and the rate of temperature decrease may be, for example, 1°C / min to 100°C / min. Alternatively, the temperature may be heated to a predetermined peak temperature without controlling the rate of temperature increase, or the temperature may not be decreased at a constant rate, but may be allowed to cool by turning off the heating source. Problems when the peak temperature is too low or too high are as explained in the method of adding the above-mentioned mixed liquid.

[0088] The heating-up method tends to produce semiconductor nanoparticles with a core-shell structure that give stronger band edge emission than when the shell is formed by the slow injection method.

[0089] Regardless of the method used to add the Group 13 element source and the Group 16 element source, the ratio of the two is preferably set to correspond to the stoichiometric composition ratio of a compound semiconductor consisting of the Group 13 element and the Group 16 element. For example, when an In source is used as the Group 13 element source and an S source is used as the Group 16 element source, the ratio is preferably set to 1:1.5 (In:S) corresponding to the composition formula of In2S3. Similarly, when a Ga source is used as the Group 13 element source and an S source is used as the Group 16 element source, the ratio is preferably set to 1:1.5 (Ga:S) corresponding to the composition formula of Ga2S3. However, the ratio does not necessarily have to be the stoichiometric composition ratio, and when the raw material is charged in an amount in excess of the amount of the desired shell to be produced, the Group 16 element source may be less than the stoichiometric composition ratio, for example, the ratio may be set to 1:1 (Group 13:Group 16).

[0090] The amounts of the Group 13 element source and the Group 16 element source may be determined so that 0.01 mmol to 10 mmol, particularly 0.1 mmol to 1 mmol, of a compound semiconductor having a stoichiometric composition consisting of a Group 13 element and a Group 16 element is generated per 10 nmol of the particle substance amount of the primary semiconductor nanoparticles. However, the particle substance amount is the molar amount when one particle is regarded as a giant molecule, and the number of nanoparticles contained in the dispersion is determined by Avogadro's number (N A =6.022×10 23 ) divided by

[0091] In the manufacturing method of this embodiment, it is preferable to form a shell containing indium sulfide or gallium sulfide by using indium acetate or gallium acetylacetonate as the Group 13 element source, elemental sulfur or dibenzyl disulfide as the Group 16 element source, and n-tetradecylamine as the dispersion liquid.

[0092] When dibenzyl disulfide is used as a group 16 element source (sulfur source) in the heating-up method, even if the holding time after reaching the peak temperature is short (for example, 20 minutes or more and 30 minutes or less), the shell is sufficiently formed, and semiconductor nanoparticles that give strong band-edge emission are easily obtained. When the shell is formed using elemental sulfur, if the holding time after reaching the peak temperature is short, it is difficult to obtain semiconductor nanoparticles with strong band-edge emission, but if the holding time is extended (for example, 40 minutes or more, particularly 50 minutes or more, with an upper limit of, for example, 60 minutes or less), semiconductor nanoparticles with strong band-edge emission are easily obtained. In addition, when elemental sulfur is used and the holding time is extended, band-edge emission with a higher emission intensity can be obtained than that of semiconductor nanoparticles prepared using dibenzyl disulfide. Furthermore, according to the heating-up method using elemental sulfur, by extending the holding time, semiconductor nanoparticles that give an emission spectrum in which the intensity of the broad peak derived from defect emission is sufficiently smaller than the intensity of the peak of band-edge emission can be obtained. Furthermore, regardless of the type of sulfur source, the longer the holding time, the more the peak of band-edge emission emitted by the obtained semiconductor nanoparticles tends to shift to the long wavelength side. Furthermore, when n-tetradecylamine is used in the dispersion liquid in the heating-up method, semiconductor nanoparticles are obtained that give an emission spectrum in which the intensity of the broad peak resulting from defect emission is sufficiently smaller than the intensity of the band-edge emission peak. The above tendency is significantly observed when a gallium source is used as the Group 13 element source.

[0093] In this way, the shell is formed to form semiconductor nanoparticles having a core-shell structure. The obtained semiconductor nanoparticles having a core-shell structure may be separated from the solvent, and may be further purified and dried as necessary. The methods of separation, purification and drying are as described above in relation to the primary semiconductor nanoparticles, and therefore detailed descriptions thereof are omitted here.

[0094] (Light Emitting Device) Next, as another embodiment of the present invention, a light-emitting device using the semiconductor nanoparticles having the core-shell structure described above will be described. The light-emitting device according to an embodiment of the present invention is a light-emitting device including a light conversion member and a semiconductor light-emitting element, and the light conversion member includes the semiconductor nanoparticles having the core-shell structure described above. According to this light-emitting device, for example, a part of the light emitted from the semiconductor light-emitting element is absorbed by the semiconductor nanoparticles having the core-shell structure to emit light of a longer wavelength. Then, the light from the semiconductor nanoparticles having the core-shell structure and the remaining part of the light emitted from the semiconductor light-emitting element are mixed, and the mixed light can be used as the light emitted by the light-emitting device.

[0095] Specifically, a light-emitting device that emits white light can be obtained by using a semiconductor light-emitting element that emits blue-violet or blue light with a peak wavelength of about 400 nm to 490 nm and a core-shell semiconductor nanoparticle that absorbs blue light and emits yellow light. Alternatively, a white light-emitting device can be obtained by using two types of core-shell semiconductor nanoparticles, one that absorbs blue light and emits green light, and one that absorbs blue light and emits red light. Alternatively, a white light-emitting device can be obtained by using a semiconductor light-emitting element that emits ultraviolet light with a peak wavelength of 400 nm or less and three types of semiconductor nanoparticles with a core-shell structure that absorb the ultraviolet light and emit blue light, green light, and red light, respectively. In this case, it is desirable to have all the light from the light-emitting element absorbed and converted by the semiconductor nanoparticles so that the ultraviolet light emitted from the light-emitting element does not leak to the outside.

[0096] Alternatively, by using a material that emits blue-green light with a peak wavelength of approximately 490 nm to 510 nm and using core-shell structured semiconductor nanoparticles that absorb the blue-green light and emit red light, a device that emits white light can be obtained. Alternatively, a light-emitting device that emits near-infrared radiation can be obtained by using a semiconductor light-emitting element that emits red light with a wavelength of 700 nm to 780 nm and semiconductor nanoparticles with a core-shell structure that absorb red light and emit near-infrared radiation.

[0097] The core-shell semiconductor nanoparticles may be used in combination with other semiconductor quantum dots or other non-quantum dot phosphors (e.g., organic or inorganic phosphors). Other semiconductor quantum dots are, for example, binary semiconductor quantum dots described in the Background Art section. As non-quantum dot phosphors, garnet phosphors such as aluminum garnet phosphors can be used. Garnet phosphors include yttrium-aluminum-garnet phosphors activated with cerium and lutetium-aluminum-garnet phosphors activated with cerium. Other examples of the non-quantum dot phosphors include nitrogen-containing calcium aluminosilicate phosphors activated with europium and / or chromium, silicate phosphors activated with europium, β-SiAlON phosphors, nitride phosphors such as CASN or SCASN, rare earth nitride phosphors such as LnSi3N11 or LnSiAlON, BaSi2O2N2:Eu or Ba3Si6O 12 Examples of phosphors that can be used include oxynitride phosphors such as N2:Eu, sulfide phosphors such as CaS, SrGa2S4, SrAl2O4, and ZnS, chlorosilicate phosphors, SrLiAl3N4:Eu phosphors, SrMg3SiN4:Eu phosphors, and K2SiF6:Mn phosphors as manganese-activated fluoride complex phosphors.

[0098] In a light-emitting device, the light conversion member containing semiconductor nanoparticles with a core-shell structure may be, for example, a sheet or plate-like member, or may be a member having a three-dimensional shape. An example of a member having a three-dimensional shape is a sealing member formed by filling a resin into a recess formed in a package of a surface-mounted light-emitting diode in order to seal the semiconductor light-emitting element when the semiconductor light-emitting element is disposed on the bottom surface of the recess.

[0099] Alternatively, another example of the light conversion member is a resin member formed to surround the upper and side surfaces of the semiconductor light emitting element with a substantially uniform thickness when the semiconductor light emitting element is arranged on a planar substrate. Alternatively, yet another example of the light conversion member is a resin member formed in a flat plate shape with a predetermined thickness on top of the semiconductor light-emitting element and the resin member containing the reflector, when the semiconductor light-emitting element is surrounded by a resin member containing a reflector so that its upper end forms the same plane as the semiconductor light-emitting element.

[0100] The light conversion member may be in contact with the semiconductor light emitting element, or may be provided at a distance from the semiconductor light emitting element. Specifically, the light conversion member may be a pellet-shaped member, a sheet member, a plate-shaped member, or a rod-shaped member that is disposed at a distance from the semiconductor light emitting element, or may be a member provided in contact with the semiconductor light emitting element, such as a sealing member, a coating member (a member that covers the light emitting element and is provided separately from the molding member), or a molding member (including, for example, a member having a lens shape). In addition, when two or more types of semiconductor nanoparticles having a core-shell structure that emit light of different wavelengths are used in a light-emitting device, the two or more types of semiconductor nanoparticles having a core-shell structure may be mixed in one light conversion member, or two or more light conversion members containing only one type of quantum dot may be combined and used. In this case, the two or more types of light conversion members may form a laminated structure or may be arranged in a dot-like or stripe-like pattern on a plane.

[0101] The semiconductor light emitting element may be an LED chip. The LED chip may have a semiconductor layer made of one or more materials selected from the group consisting of GaN, GaAs, InGaN, AlInGaP, GaP, SiC, ZnO, etc. The semiconductor light emitting element that emits blue-violet light, blue light, or ultraviolet light is preferably a semiconductor light emitting element having the general formula In X Al Y Ga 1-X-Y It is preferable that the semiconductor layer is a GaN-based compound represented by N (0≦X, 0≦Y, X+Y<1).

[0102] The light-emitting device of this embodiment is preferably incorporated as a light source in a liquid crystal display device. Since band-edge emission by semiconductor nanoparticles with a core-shell structure has a short emission lifetime, a light-emitting device using the same is suitable as a light source for a liquid crystal display device that requires a relatively fast response speed. Furthermore, the semiconductor nanoparticles with a core-shell structure of this embodiment can exhibit an emission peak with a small half-width as band-edge emission. Therefore, in the light-emitting device: - blue light having a peak wavelength in the range of 420 nm to 490 nm is obtained by a blue semiconductor light-emitting element, and green light having a peak wavelength in the range of 510 nm to 550 nm, preferably 530 nm to 540 nm, and red light having a peak wavelength in the range of 600 nm to 680 nm, preferably 630 to 650 nm is obtained by a core-shell structured semiconductor nanoparticle; or In the light-emitting device, the semiconductor light-emitting element is adapted to obtain ultraviolet light having a peak wavelength of 400 nm or less, and the core-shell structured semiconductor nanoparticles are adapted to obtain blue light having a peak wavelength of 430 nm to 470 nm, preferably 440 to 460 nm, green light having a peak wavelength of 510 nm to 550 nm, preferably 530 to 540 nm, and red light having a peak wavelength of 600 to 680 nm, preferably 630 to 650 nm. As a result, a liquid crystal display device with good color reproducibility can be obtained without using a dark color filter. The light emitting device of the present embodiment is used, for example, as a direct type backlight or an edge type backlight.

[0103] Alternatively, a sheet, plate-like member, or rod made of resin, glass, or the like, containing semiconductor nanoparticles with a core-shell structure may be incorporated into a liquid crystal display device as a light conversion member independent of the light emitting device. EXAMPLES

[0104] Example 1 (1) Preparation of primary semiconductor nanoparticles (Ag-In-S) 0.4 mmol of silver acetate (AgOAc), 0.8 mmol of thiourea, 11.8 mL of oleylamine, and 0.2 mL of 1-dodecanethiol were placed in a two-neck flask, and after vacuum degassing (3 min at room temperature), the temperature was raised to 200°C at a heating rate of 10°C / min under an Ar atmosphere. The resulting suspension was allowed to cool, then centrifuged (radius 150 mm, 2500 rpm, 10 min), and the supernatant dark red solution was taken out. Methanol was added to this until nanoparticles precipitated, and the mixture was centrifuged (radius 150 mm, 2500 rpm, 3 min), and the precipitate was vacuum dried at room temperature to obtain semiconductor nanoparticles (primary semiconductor nanoparticles).

[0105] The XRD pattern of the obtained primary semiconductor nanoparticles was measured and compared with that of tetragonal (chalcopyrite type) AgInS2, hexagonal (wurtzite type) AgInS2, and orthorhombic AgInS2. The measured XRD pattern is shown in Figure 1. From the XRD pattern, it was found that the crystal structure of the primary semiconductor nanoparticles was almost the same as that of tetragonal AgInS2. The XRD pattern was measured using a powder X-ray diffractometer (trade name SmartLab) manufactured by Rigaku Corporation (the same is true in the following experimental examples).

[0106] The shape of the obtained primary semiconductor nanoparticles was observed using a transmission electron microscope (TEM, Hitachi High-Technologies Corporation, product name H-7650), and the average particle size was measured from TEM images at 80,000 to 200,000 magnifications. Here, a Hi-Res Carbon HRC-C10 STEM Cu100P grid (Oken Shoji Co., Ltd.) was used as the TEM grid. The shape of the obtained particles was spherical or polygonal. The average particle size was determined by selecting three or more TEM images, measuring the particle size of all measurable nanoparticles contained therein, i.e., all particles except those whose particle images are cut off at the edge of the image, and calculating the arithmetic average. In all examples and comparative examples including this example, three or more TEM images were used to measure the particle size of a total of 100 or more nanoparticles. The average particle size of the primary semiconductor nanoparticles was 5.3 nm.

[0107] The amount of indium contained in the primary semiconductor nanoparticles obtained in (1) was determined by ICP emission spectroscopy (Shimadzu Corporation, ICPS-7510) to be 52.2 μmol. When the average particle size of a primary semiconductor nanoparticle is 5.3 nm, the volume of the primary semiconductor nanoparticle is 77.95 nm if it is spherical. 3 The unit cell volume of a tetragonal silver indium sulfide crystal is 0.38 nm 3 (Lattice constants 5.828 Å, 5.828 Å, 11.19 Å), and by dividing the volume of the primary semiconductor nanoparticle by the unit lattice volume, it is calculated that one primary semiconductor nanoparticle contains 205 unit lattices. Next, since one unit lattice of a tetragonal silver indium sulfide crystal contains four indium atoms, it is calculated that one nanoparticle contains 820 indium atoms. By dividing the amount of indium by the number of indium atoms per nanoparticle, the amount of substance of the primary semiconductor nanoparticles as nanoparticles is calculated to be 63.6 nmol.

[0108] (2)Shell coating Using the primary semiconductor nanoparticles obtained in (1) as the core, 20 nmol of the nanoparticles was dispersed in a mixed solvent of 5.9 mL of oleylamine and 0.1 mL of dodecanethiol to obtain a dispersion, which was kept at 200 ° C. under an Ar atmosphere. Separately, 0.8 mmol (233 mg) of indium acetate (In(OAc)3) and 1.2 mmol (38.4 mg) of sulfur powder were added to 8 mL of oleylamine and stirred at 100 ° C. for 10 minutes to dissolve the indium acetate and sulfur powder to obtain a mixed solution. 5 mL of the mixed solution was dropped into the above heated dispersion at a rate of 5 mL / h (0.5 mmol / h based on In). When the addition of the mixed solution was completed, the heating source was turned off and the solution was allowed to cool to room temperature, and then methanol was added to the solution to obtain a precipitate of semiconductor nanoparticles with a core-shell structure, and the solid components were collected by centrifugation (radius 150 mm, 2500 rpm, 3 minutes). This was dissolved in chloroform and various measurements were performed. In addition, the average particle size of the shell-coated particles was measured, and the average particle size of the core-shell semiconductor nanoparticles was found to be 11.4 nm, and the difference from the average particle size of the primary semiconductor nanoparticles indicated that the shell thickness was approximately 3.0 nm on average.

[0109] (3) Measurement of absorption, emission and excitation spectra The emission, absorption and excitation spectra were measured, and the results are shown in Figures 2 and 3, respectively. The emission spectrum was measured at an excitation wavelength of 500 nm using a multichannel spectrometer (manufactured by Hamamatsu Photonics, product name PMA12). The absorption spectrum was measured at wavelengths of 350 nm to 850 nm using an ultraviolet-visible near-infrared spectrophotometer (manufactured by JASCO, product name V-670). The excitation spectrum was measured at observation wavelengths of 593 nm and 780 nm (corresponding to the peaks observed in the emission spectrum) using a fluorescence spectrophotometer (manufactured by Horiba, Ltd., Fluoromax-4). As shown in Fig. 2, in the semiconductor nanoparticles having a core-shell structure obtained in Example 1, a steep emission peak with a half-width of about 38 nm was observed near 593 nm. Also, as shown in Fig. 3, in the excitation spectrum at an observation wavelength of 593 nm, an exciton peak was observed near 540 nm. For reference, Figs. 4 and 5 show the emission spectrum and absorption spectrum of primary semiconductor nanoparticles (Ag-In-S). The emission spectrum of Ag-In-S not covered with a shell was broad with a peak near 820 nm, and no exciton peak was observed in the absorption and excitation spectra.

[0110] In Example 1, the emission lifetime of the emission observed as a steep peak was measured. The emission lifetime was measured using a fluorescence lifetime measurement device (product name Quantaurus-Tau) manufactured by Hamamatsu Photonics K.K., and the semiconductor nanoparticles having a core-shell structure were irradiated with light of a wavelength of 470 nm as excitation light, and the decay curve of the emission near the peak wavelength of the steep emission peak was obtained. The obtained decay curve was divided into three components by parameter fitting using the fluorescence lifetime measurement / analysis software U11487-01 manufactured by Hamamatsu Photonics K.K. As a result, τ1, τ2, and τ3, as well as the contribution ratios of each component (A1, A2, and A3) were as shown in Table 1 below.

[0111] [Table 1]

[0112] As shown in Table 1, the main component (τ3, A3) was 121.7 ns, but the component (τ2, A2) with an emission lifetime of 28.0 ns was also observed at a similar intensity. This emission lifetime was the same as the fluorescence lifetime (30 ns to 60 ns) of the component with the largest contribution rate, which is the fluorescence emitted by CdSe (nanoparticles) where band edge emission has been confirmed.

[0113] Example 2 Of the primary semiconductor nanoparticles prepared in the same manner as in Example 1, 10 nmol of nanoparticle substance was dispersed in 12 mL of oleylamine to obtain a dispersion, which was kept at 260°C under an Ar atmosphere. Separately, gallium acetylacetonate (Ga(acac)3) and sulfur powder were added to oleylamine to give concentrations of 0.1 mmol / mL and 0.15 mmol / mL, respectively, and stirred at 100°C for 10 minutes to dissolve the gallium acetylacetonate and sulfur powder to obtain a mixed solution. 4 mL of the mixed solution was dropped into the above heated dispersion at a rate of 5 mL / h (0.5 mmol / h based on Ga). When the addition of the mixed solution was completed, the heating source was turned off and the solution was allowed to cool to room temperature, and then methanol was added to the solution to obtain a precipitate of semiconductor nanoparticles with a core-shell structure, and the solid components were collected by centrifugation (radius 150 mm, 2500 rpm, 3 minutes). This was dissolved in chloroform and various measurements were performed. In addition, the average particle size of the shell-coated particles was measured, and the average particle size of the core-shell semiconductor nanoparticles was 6.65 nm. The average particle size of the primary semiconductor nanoparticles produced in this example was 5.99 nm, and the difference from this indicated that the shell thickness was about 0.33 nm on average.

[0114] Although the primary semiconductor nanoparticles were produced by the same procedure as in Example 1, their average particle size was different from that produced in Example 1. This was thought to be because the time from mixing the reagents to starting heating was slightly different from that in Example 1, and the amount of silver-thiol complex expected to be generated during that time was different. The same can be said for the following Examples, etc.

[0115] Using the same apparatus as that used in Example 1, the emission spectrum (excitation wavelength 450 nm), absorption spectrum, and excitation spectrum at observation wavelengths of 580 nm and 730 nm were measured. The results are shown in Figures 6 and 7. As shown in Figure 6, in the core-shell semiconductor nanoparticles obtained in Example 2, a steep emission peak with a half-width of about 39 nm was observed near 584 nm. In addition, as shown in Figure 7, in the excitation spectrum at an observation wavelength of 580 nm, an exciton peak was observed near 530 nm. Furthermore, the luminescence quantum yield at a steep peak (530-650 nm) thought to be band edge emission was measured using the same multichannel spectrometer (excitation wavelength 450 nm) as in Example 1, and was found to be 1.9%. In addition, the luminescence lifetime of the luminescence observed as a steep peak was measured in the same manner as in Example 1, and the values ​​of τ1, τ2, and τ3, as well as the contribution ratios of each component (A1, A2, and A3) were as shown in Table 2. As shown in Table 2, the luminescence lifetime of the main component (τ2, A2) was 39.1 ns.

[0116] [Table 2]

[0117] Example 3 Of the primary semiconductor nanoparticles produced by the same procedure as in Example 1, 30 nmol of nanoparticle substance amount, 0.1 mmol of gallium acetylacetonate (Ga(acac)3), 0.05 mmol of dibenzyl disulfide, and 12 mL of oleylamine were placed in a flask, heated to 260°C at a heating rate of 10°C / min, and held at 260°C for 20 minutes, after which the heating source was turned off and the solution was allowed to cool. Methanol was then added to the solution to obtain a precipitate of semiconductor nanoparticles with a core-shell structure, and the solid component was collected by centrifugation (radius 150 mm, 2500 rpm, 3 minutes). This was dissolved in chloroform and various measurements were performed. In addition, the average particle size of the shell-coated particles was measured, and the average particle size of the core-shell semiconductor nanoparticles was 8.0 nm. The average particle size of the primary semiconductor nanoparticles produced in this example was 6.0 nm, and the difference from this indicated that the shell thickness was about 1 nm on average.

[0118] The same apparatus as that used in Example 1 was used to measure the emission spectrum (excitation wavelength 450 nm), absorption spectrum, and excitation spectrum. The results are shown in FIG. 8 and FIG. 9, respectively. As shown in FIG. 8, in the semiconductor nanoparticles having a core-shell structure obtained in Example 3, a steep emission peak with a half-width of about 39 nm was observed near 586 nm. Also, as shown in FIG. 9, in the excitation spectrum at an observation wavelength of 585 nm, an exciton peak was observed near 535 nm. Furthermore, when the emission quantum yield was measured in the same manner as in Example 2, the emission quantum yield was 14.3%. In addition, the luminescence lifetime of the luminescence observed as a steep peak was measured in the same manner as in Example 1, and the values ​​of τ1, τ2, and τ3, as well as the contribution ratios of each component (A1, A2, and A3) were as shown in Table 3. As shown in Table 3, the luminescence lifetime of the main component (τ2, A2) was 51.4 ns.

[0119] [Table 3]

[0120] When the emission spectra of the semiconductor nanoparticles obtained in Example 1 and the semiconductor nanoparticles obtained in Example 2 were compared, the emission intensity of the steep peak (band edge emission intensity) was clearly greater than the emission intensity of the broad peak (defect emission intensity) in Example 2. x The shell formation by InS x It can be seen that this is more advantageous for obtaining band-edge emission from the core than shell formation by the SiO2 method.

[0121] When the luminescence quantum yield of the semiconductor nanoparticles obtained in Example 2 and the semiconductor nanoparticles obtained in Example 3 was compared, it was confirmed that the luminescence quantum yield of Example 3 was 7.5 times that of Example 2. Furthermore, during shell formation, even though the molar ratio of the Ga source for shell formation to the primary semiconductor nanoparticles was the same, the shell thickness in Example 3 was large at about 1 nm. In consideration of these facts, it is presumed that when dibenzyl disulfide was used as the sulfur source, the shell covered the surface of the core without interruption, effectively removing surface defects of the core, thereby increasing the intensity of the band edge luminescence.

[0122] Comparative Example 1 Of the primary semiconductor nanoparticles prepared in the same manner as in Example 1, 10 nmol of nanoparticle substance was dispersed in 12 mL of oleylamine to obtain a dispersion liquid, which was kept at 260°C under an Ar atmosphere. Separately, zinc acetate (Zn(OAc)2) and sulfur powder were added to oleylamine so that each was 0.1 mmol / mL, and the mixture was obtained by dissolving the zinc acetate and sulfur powder by heating at 100°C for 10 minutes. 2 mL of the mixture was dropped into the above heated dispersion liquid at a rate of 5 mL / h (0.5 mmol / h based on Zn). When the addition of the mixture liquid was completed, the heating source was turned off and the mixture was allowed to cool to room temperature, and then methanol was added to the solution to obtain a precipitate of semiconductor nanoparticles with a core-shell structure, and the solid components were collected by centrifugation (radius 150 mm, 2500 rpm, 3 minutes). This was dissolved in chloroform, and the emission spectrum (excitation wavelength 450 nm) and absorption spectrum were measured using the same device as that used in Example 1. The results are shown in Figures 10 and 11.

[0123] As shown in Fig. 10, in the nanoparticles obtained in Comparative Example 1, a sharp emission peak as seen in Examples 1 to 3 was not observed, and a broad spectrum was observed. That is, although ZnS has a larger band gap energy than Ag-In-S and can provide type-1 band alignment, no band edge emission was observed. This is considered to be due to the formation of a solid solution between the core and shell, and no core-shell structure was formed.

[0124] (Examples 4A to 4D) Of the primary semiconductor nanoparticles prepared by the same procedure as in Example 1, 30 nmol in terms of the amount of substance as nanoparticles, 0.1 mmol of gallium acetylacetonate (Ga(acac)3), 0.05 mmol of dibenzyl disulfide, and 12 mL of oleylamine were placed in a flask and heated to 260°C at a heating rate of 10°C / min. Immediately after reaching 260°C (Example 4A), they were held at 260°C for 10 minutes (Example 4B), 20 minutes (Example 4C), and 30 minutes (Example 4D), respectively, and then the heating source was turned off and the mixture was allowed to cool. Thereafter, the liquid containing the reaction product was centrifuged (radius 150 mm, 2500 rpm, 10 minutes) and the supernatant was taken out. Methanol was added to this until precipitation of nanoparticles occurred, and the mixture was centrifuged (radius 150 mm, 2500 rpm, 5 minutes) to recover the solid component. This was dissolved in chloroform and various measurements were performed.

[0125] (Examples 5A to 5F) Of the primary semiconductor nanoparticles produced by the same procedure as in Example 1, 30 nmol in terms of the amount of substance as nanoparticles, 0.1 mmol of gallium acetylacetonate (Ga(acac)3), 0.15 mmol of sulfur, and 12 mL of oleylamine were placed in a flask and heated to 260°C at a heating rate of 10°C / min. Immediately after reaching 260°C (Example 5A), the mixture was held at 260°C for 10 minutes (Example 5B), 30 minutes (Example 5C), 40 minutes (Example 5D), 50 minutes (Example 5E), and 60 minutes (Example 5F), respectively, and then the heating source was turned off and the mixture was allowed to cool. Thereafter, the liquid containing the reaction product was centrifuged (radius 150 mm, 2500 rpm, 10 minutes), and the supernatant was taken out. Methanol was added to this until precipitation of nanoparticles occurred, and the mixture was centrifuged (radius 150 mm, 2500 rpm, 5 minutes) to recover the solid component. This was dissolved in chloroform and various measurements were carried out.

[0126] The emission spectra (excitation wavelength 400 nm) of the semiconductor nanoparticles obtained in Examples 4A to 4D and Examples 5A to 5F were obtained using the same apparatus as that used in Example 1. The emission spectra are shown in Figure 12 (Examples 4A to 4D) and Figure 13 (Examples 5A to 5F). Note that in both figures, the emission spectra of primary semiconductor nanoparticles (cores) without a shell are also shown as a reference example.

[0127] As shown in FIG. 12, among Examples 4A to 4C in which a shell was formed using dibenzyl disulfide as a sulfur source, Example 4C (holding time 20 minutes) had the highest band edge emission peak intensity. Example 4D (holding time 30 minutes) showed a lower band edge emission peak intensity than Example 4C. This shows that when a shell is formed using dibenzyl disulfide, the band edge emission intensity can be improved with a relatively short holding time. This can also be confirmed by FIG. 14, which shows the relationship between the band edge emission peak intensity and holding time for Examples 4A to 4C.

[0128] As shown in FIG. 13, among Examples 5A to 5F in which a shell was formed using elemental sulfur as the sulfur source, Example 5E (holding time 50 minutes) had the highest band edge emission peak intensity. From this, it can be seen that when a shell is formed using elemental sulfur as the sulfur source, a long holding time is required to obtain particles with a core-shell structure having a higher band edge emission peak intensity. This can also be confirmed by FIG. 14, which shows the relationship between the band edge emission peak intensity and the holding time for Examples 5A to 5F. In addition, as shown in FIG. 14, when a shell is formed using elemental sulfur with a long holding time, a band edge emission peak intensity greater than the maximum value of the band edge emission peak intensity achieved when dibenzyl disulfide is used can be achieved.

[0129] Furthermore, as shown in FIG. 13, when a shell was formed by using elemental sulfur for a long holding time, the band edge emission intensity (ratio of band edge emission / defect emission intensity) could be increased (particularly in Examples 5E and 5F).

[0130] 15 is a graph showing the relationship between the peak wavelength of band edge emission and the retention time for Examples 4A to 4D and 5A to 5F. It can be seen that in both cases where dibenzyl disulfide and elemental sulfur are used, the peak wavelength shifts to the longer wavelength side as the retention time increases.

[0131] [HRTEM and HAADF observations] The core-shell structured semiconductor nanoparticles of Example 5F were observed by HRTEM and HAADF (manufactured by JEOL Ltd., product name ARM-200F). The HRTEM image is shown in Figure 16, and the HAADF image is shown in Figure 17. In both cases, a crystalline core having a regular pattern and a shell not having a regular pattern located around it were observed, and it was observed that the shell in the semiconductor nanoparticles of Example 5F was amorphous.

[0132] [XPS analysis] The core-shell structured semiconductor nanoparticles of Example 5F were analyzed by X-ray photoelectron spectroscopy (Shimadzu Corporation, product name KRATOS AXIS-165X). When the peak positions derived from the 3d orbital of silver and indium were compared with the database, it was confirmed that they matched the positions of sulfides, and when the peak positions derived from the 2p orbital of sulfur were compared with the database, it was confirmed that they matched the positions of metal sulfides. In addition, for gallium, it was not possible to confirm that it was a sulfide because a database of sulfides was not available, but it was confirmed that the peak positions derived from the 3d orbital of gallium were clearly different from those of metal gallium and were located between gallium oxide and gallium selenide, so that it was highly likely to be a sulfide.

[0133] [Analysis using energy dispersive X-ray analyzer] The atomic percentage of each element contained in the core-shell semiconductor nanoparticles of Example 5F was analyzed using an energy dispersive X-ray analyzer (manufactured by EDAX, product name OCTANE). The results are shown in Table 4. When the composition was AgInS2·Ga2S3, the atomic percentage of sulfur calculated from the results of Ag and Ga in Table 4 was 53.9 (17.2×2+13.1÷2×3=53.9), which showed good agreement with the value of S in Table 4.

[0134] [Table 4] Example 6 (1) Preparation of primary semiconductor nanoparticles (Ag-In-S) 0.4 mmol of silver acetate (AgOAc), 0.8 mmol of thiourea, 35.8 mmol of n-tetradecylamine, and 0.2 mL of 1-dodecanethiol were placed in a two-neck flask, and after vacuum degassing (3 min at room temperature), the temperature was raised to 150°C at a heating rate of 5°C / min under an Ar atmosphere. The resulting suspension was allowed to cool, and when the temperature fell below 90°C, a small amount of hexane was added, followed by centrifugation (radius 150 mm, 4000 rpm, 10 min), and the supernatant dark red solution was taken out. Methanol was added to this until nanoparticles precipitated, and the mixture was centrifuged (radius 150 mm, 2500 rpm, 3 min), and the precipitate was vacuum dried at room temperature to obtain semiconductor nanoparticles (primary semiconductor nanoparticles).

[0135] (2)Shell coating Using the primary semiconductor nanoparticles obtained in (1) as the core, 30 nmol of the nanoparticles, 0.1 mmol of gallium acetylacetonate (Ga(acac)3), 0.15 mmol of sulfur, and 36.48 mmol of n-tetradecylamine were placed in a flask and heated to 260°C at a heating rate of 10°C / min, and kept at 260°C for 50 minutes, after which the heating source was turned off and the solution was allowed to cool. Methanol was then added to the solution to obtain a precipitate of semiconductor nanoparticles with a core-shell structure, and the solid component was collected by centrifugation (radius 150 mm, 2500 rpm, 3 minutes). This was dissolved in chloroform and various measurements were performed. Furthermore, when the average particle size of the shell-coated particles was measured, the average particle size of the core-shell semiconductor nanoparticles was 8.6 nm. The average particle size of the primary semiconductor nanoparticles produced in this example was 7.1 nm, and the difference from this indicated that the shell thickness was about 0.75 nm on average.

[0136] The emission spectrum (excitation wavelength 450 nm) and absorption spectrum were measured using the same device as that used in Example 1. The results are shown in FIG. 18 and FIG. 19, respectively. As shown in FIG. 18, in the semiconductor nanoparticles having a core-shell structure obtained in Example 6, a steep emission peak with a half-width of about 28 nm was observed near 581 nm. Also, as shown in FIG. 19, in the excitation spectrum at an observation wavelength of 585 nm, an exciton peak was observed near 535 nm. Furthermore, the emission quantum yield at the steep peak (530-630 nm), which is thought to be band edge emission, was measured using the same multichannel spectrometer (excitation wavelength 450 nm) as in Example 1, and was found to be 21.1%. [Industrial Applicability]

[0137] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS Embodiments of the present invention are semiconductor nanoparticles capable of band-edge emission and can be used as wavelength conversion materials in light-emitting devices or as biomolecular markers.

Claims

1. M 1 , M. 2 and Z, 1 is at least one element selected from the group consisting of Ag, Cu and Au, and contains at least Ag; M 2 a first semiconductor being a chalcopyrite-type semiconductor, wherein Z is at least one element selected from the group consisting of Al, Ga, In, and Tl, and contains at least In, and Z is at least one element selected from the group consisting of S, Se, and Te, and contains at least S; a second semiconductor disposed over a surface of the first semiconductor and having a band gap energy greater than that of the first semiconductor; the second semiconductor is composed of a Group 13 element including at least one selected from Ga and In, and a Group 16 element including at least S; A semiconductor nanoparticle that emits light when irradiated with light and has a luminescence lifetime of 200 ns or less.

2. The semiconductor nanoparticles according to claim 1 , which emit light having an emission spectrum with a half-width of 50 nm or less.

3. 3. The semiconductor nanoparticles according to claim 1, which emit light having a peak wavelength of 430 nm to 470 nm, 510 nm to 550 nm, or 600 nm to 680 nm when irradiated with light having a peak wavelength in the range of 400 nm to 490 nm.

4. 4. The semiconductor nanoparticles according to claim 1, having an average particle size of 1 nm to 20 nm.

5. The semiconductor nanoparticles according to any one of claims 1 to 4, wherein the first semiconductor has an average particle size of 2 nm to 10 nm.

6. A light conversion member comprising the semiconductor nanoparticles according to any one of claims 1 to 5.

7. The light conversion member according to claim 6 , which is a sheet or plate-like member.

8. A semiconductor light emitting element that emits light having a peak wavelength in the range of 400 nm to 490 nm; A light-emitting device comprising the light conversion member according to claim 6 or 7.

9. A liquid crystal display device comprising the light emitting device according to claim 8.

10. A semiconductor light emitting element that emits light having a peak wavelength in the range of 400 nm to 490 nm; A liquid crystal display device comprising the light conversion member according to claim 6 or 7.

Citation Information

Patent Citations

  • CuInS2 / In2S3 / ZnS fluorescent quantum dot adopting double-layer core-shell structure and preparation method of CuInS2 / In2S3 / ZnS fluorescent quantum dot

    CN104861964A

  • Manufacturing method of semiconductor nanoparticle, and semiconductor nanoparticle

    JP2010031115A

  • Light emitting diode unit and display device including the same

    JP2010177656A

  • Manufacturing of electroactive films based on multilayer structure

    JP2010525566A

  • Semiconductor nanoparticle and method for producing the same

    JP2011178645A